2006
DOI: 10.1080/02786820600714403
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Peak Inert-Mode Temperature on Elemental Carbon Measured Using Thermal-Optical Analysis

Abstract: Thermal-optical analysis is a conventional method for classifying carbonaceous aerosols as organic carbon (OC) and elemental carbon (EC). This article examines the effects of three different temperature protocols on the measured EC. For analyses of parallel punches from the same ambient sample, the protocol with the highest peak helium-mode temperature (870• C) gives the smallest amount of EC, while the protocol with the lowest peak helium-mode temperature (550 • C) gives the largest amount of EC. These differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
131
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(147 citation statements)
references
References 26 publications
13
131
3
Order By: Relevance
“…14,15,17,22,27 PC generally has a higher light-absorbing efficiency than native EC, which mostly demands that, prior to the split point in the He/O 2 mode, more light-absorbing carbon (LAC, including native EC and PC) be burned to compensate for the charring-caused laser signal decreases, resulting in a lower EC in the NIOSH protocol. 15 The third factor is the laser pattern for the charring correction (reflection or transmission). Studies have revealed that PC is always distributed throughout the filter section rather than only on or close to the filter's outer surface.…”
Section: ' Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…14,15,17,22,27 PC generally has a higher light-absorbing efficiency than native EC, which mostly demands that, prior to the split point in the He/O 2 mode, more light-absorbing carbon (LAC, including native EC and PC) be burned to compensate for the charring-caused laser signal decreases, resulting in a lower EC in the NIOSH protocol. 15 The third factor is the laser pattern for the charring correction (reflection or transmission). Studies have revealed that PC is always distributed throughout the filter section rather than only on or close to the filter's outer surface.…”
Section: ' Materials and Methodsmentioning
confidence: 99%
“…First, apart from OC abundance, there are also other possible causes for the discrepancy between NIOSH and IMPROVE protocols. For example, brown carbon can badly influence the OC/EC split, 30 metals in the sample can start to remove EC already in the inert gas mode, 18 heavily loaded filter can change laser attenuation coefficient and charring rate, 15,27 and differing abundances of SOA may have inconsistent influence on laser correction. 46 More importantly, the equation was deduced from coal-burning samples (Group I) and was directly verified by only 13 source samples and 20 urban samples (Group II), and more comprehensive and systematic verifications should be carried out for ambient samples with various regional features, difficult as this may be.…”
Section: Articlementioning
confidence: 99%
See 1 more Smart Citation
“…• C) by minerals in the aerosol particles or collection substrates (Chow et al 2001(Chow et al , 2004Subramanian et al 2006). We propose here to use positive matrix factorization (PMF) to apportion the evolved C peaks (OC 1 -OC 4 and EC 1 -EC 5 ) to OC and EC.…”
Section: Ec and Oc Analysismentioning
confidence: 99%
“…It has also been shown that PC defined by different temperature protocols can differ significantly (Subramanian et al 2006). Therefore, another issue associated with PC involves the choice of the charring correction method-transmittance or reflectance.…”
Section: ¡3mentioning
confidence: 99%